Effect of melatonin implants on the dry period of dairy goats - JIMÉNEZ, ANTONIO; SΑNCHEZ JOAQUÍN; ANDRÉS, SANTIAGO (The Indian Journal of Animal Sciences, 2014)
The melatonin administration to milking goats before mating increased significantly blood glutathione peroxidase, glutathione reductase and superoxide dismutase activities during 3–4 months. Therefore, the use of melatonin implants, in addition to reproductive benefits, could affect milk production through improving the health of the udder during the dry period in dairy goats.